The use of technologies in the development of children with Autism Spectrum Disorder (ASD) (Research, Society and Development, 2022)
The objective of this research is to analyze and reflect on how the use of technologies methodologically facilitates the cognitive development of children with Autism Spectrum Disorder (ASD), and its importance in cognitive development and learning. We tried to show how technology helps and can influence the intervention process, stimulating the cognitive functions of these subjects. The results showed that the didactics to be used for students with ASD demands, above all, the implementation of existing technologies by the school to facilitate the teaching-learning of students with ASD. In this sense, the use of new technologies is of great value making a difference in the acquisition of knowledge and social skills, contributing significantly to cognitive and social development.